International trade, regional integration and food security in the Middle East - DeRosa, Dean A. (International Food Policy Research Institute, 1995)
Against the background of increasing interest in closer economic relations in the Middle East, the contribution that greater integration of markets might make to improving food security in the region is investigated, using a quantitative framework for gauging the reduction in instability of market supplies for cereal, meat, and dairy commodities under regional cooperation schemes versus more general policies to increase the integration of Middle East markets with markets in Western Europe and the world at large. Nondiscriminatory trade liberalization yields the greatest improvements in food security, but expansion of intra-regional trade relations also result in improved food security, except in the case of wheat and other cereals because of already extensive Middle East imports of these commodities commercially and under bilateral and multilateral food aid programs.